The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fnins.2015.00187
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hypothalamic neuropeptides gene expression in diet induced obesity resistant rats: possible targets for obesity prediction?

Abstract: Several factors play a role in obesity (i.e., behavior, environment, and genetics) and epigenetic regulation of gene expression has emerged as a potential contributor in the susceptibility and development of obesity. To investigate the individual sensitivity to weight gain/resistance, we here studied gene transcription regulation of several hypothalamic neuropeptides involved in the control of energy balance in rats developing obesity (diet-induced obesity, DIO) or not (diet resistant, DR), when fed with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 49 publications
3
53
1
1
Order By: Relevance
“…We have subsequently investigated whether EM66 expression within the hypothalamus is influenced by the energy status of the animal, and we have compared it with the gene expression of POMC and NPY in diet‐induced obesity and in fasting conditions. Our results reveal that long‐term HFD exposure is associated with an important decrease in POMC mRNA levels and no significant change in NPY gene expression, in agreement with previous studies . Concurrently, we show that expression of SgII (the EM66 precursor) is down‐regulated in HFD mice to a similar extent as POMC, suggesting that EM66 is a major anorexigenic factor playing a crucial role in the maintenance of the obese status, acting in synergy with α‐MSH (the anorexigenic POMC‐derived peptide).…”
Section: Discussionsupporting
confidence: 91%
“…We have subsequently investigated whether EM66 expression within the hypothalamus is influenced by the energy status of the animal, and we have compared it with the gene expression of POMC and NPY in diet‐induced obesity and in fasting conditions. Our results reveal that long‐term HFD exposure is associated with an important decrease in POMC mRNA levels and no significant change in NPY gene expression, in agreement with previous studies . Concurrently, we show that expression of SgII (the EM66 precursor) is down‐regulated in HFD mice to a similar extent as POMC, suggesting that EM66 is a major anorexigenic factor playing a crucial role in the maintenance of the obese status, acting in synergy with α‐MSH (the anorexigenic POMC‐derived peptide).…”
Section: Discussionsupporting
confidence: 91%
“…In the studies evaluated herein, no methylation changes were observed for NPY, MC4R, or PPAR-γ when investigated (Cifani et al, 2015;Zheng et al, 2015), while the methylation status of POMC was consistently found to be altered and positively associated with increased levels of leptin and insulin and the development of the obesity phenotype and symptoms of MeS (Cifani et al, 2015;Gali Ramamoorthy et al, 2018;Marco et al, 2013;Andreas Plagemann et al, 2009;Wang et al, 2014;Zhang et al, 2014;Zheng et al, 2015).…”
Section: P Om C Me Thyl Ati On and Ob E S It Ymentioning
confidence: 68%
“…In the studies evaluated herein, no methylation changes were observed for NPY , MC4R, or PPAR‐ γ when investigated (Cifani et al, ; Zheng et al, ), while the methylation status of POMC was consistently found to be altered and positively associated with increased levels of leptin and insulin and the development of the obesity phenotype and symptoms of MeS (Cifani et al, ; Gali Ramamoorthy et al, ; Marco et al, ; Andreas Plagemann et al, ; Wang et al, ; Zhang et al, ; Zheng et al, ). With POMC‐mediated leptin and insulin function playing a major role in the pathological development of obesity and MeS, the methylation status of POMC thus represents a pivotal therapeutic target.…”
Section: Pomc Methylation and Obesitymentioning
confidence: 92%
See 1 more Smart Citation
“…The increase in POMC and NPY expression detected in the brains of E18 pups taken from dams fed a high fat diet is somewhat paradoxical. Indeed, one would expect that POMC expression would be decreased as it does in adult animals that are chronically exposed to high fat diets (Cifani et al, 2015; Desai et al, 2016). Nevertheless, our data are consistent with data of others showing that rat pups whose mother was exposed to a high fat diet showed increased POMC and NPY mRNA expression in the ARC twenty days after birth (Chen and Morris, 2009).…”
Section: Discussionmentioning
confidence: 99%